Theory and best practice models in educational institutions in Spain and Italy - Profanter, Annemarie, 1976-; Sevillano García, Ma. Luisa (María Luisa) (Cambridge Scholars Publishing, 2017)
The current societal and social reality in Europe is undergoing far-reaching changes due to the phenomenon of migration. Educational policy and pedagogical practice play a key role in the academic support of immigrant children in schools. In this volume, the connections between societal change and educational issues in relation to two southern European nations, Spain and Italy, are analyzed. The stories of intercultural communication and integration of these two case studies focus on five themes: linguistic diversity, the performance gap, teacher training programs and school culture, the role of music education in multicultural and multilingual contexts, and the development of a supranational education as an improvement for multicultural education. The volume is of particular relevance for educational researchers, as well as for the interested general reader. It takes the reader to public and private entities in Italy and Spain, where intercultural education is part of societal discourse, and serves as a sounding board for the discussion of developments in other parts of Europe with similar demographics.